2020
DOI: 10.1101/2020.03.24.20042382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viral Kinetics and Antibody Responses in Patients with COVID-19

Abstract: Background A pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been spreading over the world. However, the viral dynamics, host serologic responses, and their associations with clinical manifestations, have not been well described in prospective cohort. Methods We conducted a prospective cohort and enrolled 67 COVID-19 patients admitting between Jan 26 and Feb 5, 2020. Clinical specimens including nasopharyngeal swab, sputum, blood, urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
341
3
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(392 citation statements)
references
References 20 publications
38
341
3
10
Order By: Relevance
“…For example, using an ELISA in-house developed method, Zhang et al found that the increase of antibody against the virus was clearly visible in almost all patients after 5 days of symptom onset, a time period that was usually considered as a transition from an early to a late period of infection [19]. Likewise, using a commercial ELISA kit from Livzon Diagnostics (China), Tan et al found a marked increase of immunoglobulins 7 days after the onset of symptoms, particularly in patients with severe disease [20]. Table 3 reports in detail the kinetics of IgM and IgG, showing that IgG requires at least 12 days to attain 100% sensitivity, whilst the highest positive rate achieved for IgM was 88% throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using an ELISA in-house developed method, Zhang et al found that the increase of antibody against the virus was clearly visible in almost all patients after 5 days of symptom onset, a time period that was usually considered as a transition from an early to a late period of infection [19]. Likewise, using a commercial ELISA kit from Livzon Diagnostics (China), Tan et al found a marked increase of immunoglobulins 7 days after the onset of symptoms, particularly in patients with severe disease [20]. Table 3 reports in detail the kinetics of IgM and IgG, showing that IgG requires at least 12 days to attain 100% sensitivity, whilst the highest positive rate achieved for IgM was 88% throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used biomarkers for the detection of SARS-CoV-2 infection in commercial immunoassays (rapid lateral flow immunoassay (LFIA) tests, automated chemiluminescence immunoassay (CLIA), manual ELISA, and other formats) are IgM and IgG antibodies produced in suspects from the 2nd week of viral infection. IgM can be detected in the patient samples from 10 to 30 days after SARS-CoV-2 infection, while IgG can be detected from 20 days onwards [13]. The IgM response occurs earlier than that of IgG, but it then decreases and disappears.…”
Section: Ofmentioning
confidence: 94%
“…Another study 40 suggested that weaker antibody responses to endemic HCoVs (specifically HCoV-229E) might be because these mainly infect the upper respiratory tract. Preliminary studies on SARS-CoV-2 point to a possibly contrasting pattern to MERS-CoV: while IgM antibodies appear at the same time in severe and non-severe cases, IgG appears sooner in severe cases 33 . On the other hand, neutralizing antibody titers were higher in severe cases 34 .…”
Section: Correlation Between Severe Disease and Rise In Post-infectiomentioning
confidence: 98%
“…A comparison of a cohort of [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] year-olds and a cohort of ≥65 year-olds found no clear difference in incidence between the two age groups, as measured by seroconversion or PCRconfirmed, HCoV-associated respiratory illness 120 . Finally, observational studies have shown evidence of coronavirus-associated respiratory illnesses in elderly populations [121][122][123] and across all ages 124 .…”
Section: Seroincidence Of Endemic Coronaviruses Occurs In All Age Gromentioning
confidence: 99%